Corrosion Behavior of AISI 1018 Carbon Steel in Localized Repairs of Mortars with Alkaline Cements and Engineered Cementitious Composites - Maldonado Bandala, Erick; Higueredo Moctezuma, Noema; Nieves Mendoza, Demetrio; Gaona Tiburcio, Citlalli; Zambrano Robledo, Patricia del Carmen; Hernández Martínez, Héctor; Almeraya Calderón, Facundo (Molecular Diversity Preservation International, 2020)
The selection of materials for repairs of reinforced concrete structures is a serious concern. They are chosen for the mechanical capacity that the repair mortar achieves. However, several important characteristics have been left aside, such as the adhesion of the repair mortar with the concrete substrate, the electrical resistivity and—hugely important—the protection against corrosion that the repair material can provide to the reinforcing steel. The aim of this work was to study the corrosion behavior of AISI 1018 carbon steel (CS) in mortars manufactured with alkaline cements, engineered cementitious composites (ECC), and supplementary cementitious materials (SCM). Two types of ordinary Portland cement (OPC) 30R and 40R were used. The constituent materials for the mortars with ECC mixture mortars they use OPC 40R, class F fly ash (FA), silica fume (SF) and polypropylene (PP) fibers. The sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) were used as activating agents in alkali activated cements. The reinforced specimens were immersed in two different electrolytes, exposed to a 3.5 wt % of NaCl and Na2SO4 solutions, for 12 months and their electrochemical behavior was studied by half-cell potential (Ecorr) and linear polarization resistance (LPR) according to ASTM C876-15 and ASTM G59-97, respectively. The results obtained indicated that, the mortar they have the best performance and durability, is the conventional MCXF mortar, with OPC 30R and addition of 1% polypropylene PP fiber improves the behavior against the attack of chlorides and sulfates